UPAYA PENINGKATAN PARTISIPASI ORANG MUDA KATOLIK (OMK) DALAM KEGIATAN GEREJA DI PAROKI ST. ALFONSUS DE LIGUORI LEWOTALA - Maria Kristina Bulu; Fransiska Peni Hadjon; Felisitas Ose Sogen (Adiba Aisha Amira, 2026)
The participation of Catholic Youth (OMK) in church life plays a crucial role in maintaining the continuity of the Church's ministry and development. However, in reality, OMK's involvement in various church activities at St. Alfonsus De Liguori Parish, Lewotala, still faces various challenges, such as low motivation, the influence of technological developments, busy educational and work schedules, and the lack of attractive youth development programs. This community service activity aims to identify factors that influence the low participation of OMK and to formulate efforts to increase their involvement in church activities. The method used is a qualitative descriptive approach through observation, interviews, and mentoring of OMK members and church administrators. The results of the activity indicate that increasing OMK participation can be achieved through continuous faith development, active involvement of OMK in liturgical and social activities, the provision of creative activities based on youth interests, and strengthening communication between church administrators and OMK. In addition, support from the pastor, parish administrators, and families is also an important factor in encouraging youth involvement in church life. With these efforts, OMK is expected to become a generation of the Church that is active, responsible, and has a high spirit of service.